THE SURFACE MINER SUSTAINABLE TECHNOLOGY INTRODUCTION FOR OIL-SHALE MINING IN ESTONIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The paper introduces a high-selective oil-shale mining technology and the first results of surface miner Wirtgen 2500SM tests. The technology allows to decrease oil-shale loses from 10-15% up to 5-7%. Mining process of the surface miner has a lower disturbing impact, which is topical in open pits and quarries especially in densely populated areas. The low level of dust and noise emissions and also very’ low vibration are arguments to mine oil shale with surface miner instead of drilling-blasting operations. The risk analysis for testing technology was elaborated.